Termination of Pregnancy in a Patient with Advanced Ovarian Cancer - Özdemir, Suna; Çelik, Çetin; Gezginç, Kazım; Esen, Hasan (Gynecology Obstetrics & Reproductive Medicine, 2010)
Ovarian cancer during pregnancy is a rare entity and the management of the disease can be challenging for the patient and the clinician. In this case, we report a case of advanced ovarian carcinoma diagnosed during pregnancy, which was managed with termination of pregnancy and chemotheraphy. The patient was underwent exploratory laparatomy including the right ovarian cystectomy, omentectomy, appendectomy, pelvic and para-aortic lymphadenectomy after frozen section of borderline serous cystadenocarcinoma at the 14 week of gestation. After final histopathology, the patient was staged as having FIGO stage IIIC disease. The pregnancy was termineted with the decision of patient and her family. The patient was treated with chemotheraphy.